Spontaneous splenic rupture in a patient with infectious mononucleosis - Baker, Charlotte Ruth (BMJ Case Rep, 2019)
We present a case of spontaneous, atraumatic splenic rupture secondary to Epstein-Barr virus (EBV) infection, in a young, female patient. Splenic rupture is a rare complication of EBV infection, but is associated with the highest mortality. Additionally, this case illustrates the diagnostic challenge in a patient presenting in atypical manner, with only left-sided pleuritic chest pain, and lacking any of the classical tonsillitis symptoms associated with EBV infection.